ZnO/bentonite Nanocomposites Prepared with Solid-state Ion Exchange as Photocatalysts - Bahareh Hakimi (Journal of Ultrafine Grained and Nanostructured Materials, 2018)
Photocatalyst nanocomposites of ZnO/bentonite clay are synthesized by Solid-state ion exchange method. Ion exchange intercalation process of clays is used to incorporate the catalyst into the basal space of the layered structure of clays. The purpose of this study is to find a new method, which is focused on simplifying and saving time to prepare ZnO-bentonite composite with photocatalyst property. The synthesis of ZnO-doped bentonite nanocomposite is accomplished by placing bentonite in a melting bath of ZnSO4 for 10, 20, 40, 60 and 90 min. The nanocomposites are characterized by morphological (SEM), optical (UV/vis reflection) and analytical (EDX) techniques. According to SEM results, after ion exchanging, the parent structure of bentonite remains and only the distance between flakes increased significantly. EDX analysis clearly suggest the success of ion exchange of the expense of Ca2+, Na+ and Mg2+ cations with Zn2+. The calculated band gap for the composites were 3.14 eV (10 min), 2.64 eV (20 min) and 2.54 eV at longer times, respectively. All the prepared composites showed acceptable degradation performances. The greatest photocatalytic activity is detected in ZnO/bentonite composite solid-state ion exchanges which lasts 60 and 90 min. Leaching test results showed that the concentrations of Zn are less than 4 mg/l between 0 and 6 h. These results indicated that the photocatalytic property of composites would last longer.